Dalit women speak out : Caste, class and gender violence in India - S.J., Aloysius Irudayam Mangubhai, Jayshree P. Lee, Joel G. (Zubaan, 2011)
The right to equality ragardless of gender and caste is a fundamental right in India. However, the Indian government has acknowledged that institutional forces arraiged against the right are powerful and shape people's midsts to accept pervasive gender and caste inequality. This is no more apparent then when one visits Dalit women living in their caste-segregated localities. Vulnerably positioned at the bottom of India's gender, caste and class heirarchies, Dalit women experiences the outcome of severely imbalanced social, economic and political power equations in terms of endemic caste-class-gender discrimination and violence. The study presents an analytical overview of the complexities of systemic violence that Dalit women face through an analysis of 500 Dalit women's narratives across four states. Excerpts of these narratives are utilized to illustrate the wider trends and patterns of different manifestations of violence against Dalit women. The study calls for the implementation of comprehensive preventive and punishment measures to eradicate caste-class-gender discrimination and violence against Dalit women in both public and private life, in conjunction with measures to fulfil their human rights.